Sintesis Karbon Aktif dari Kulit Salak Aktivasi Kimia-Senyawa KOH sebagai Adsorben Proses Adosprsi Zat Warna Metilen Biru - Arenst Andreas (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2015)
In this study, activated carbons were prepared through chemical activation of Salacca peel, using KOH as chemical agent. Salacca peels were firstly pre-carbonized in an electrical furnace at temperature of 500 °C, then the peels were impregnated at a fixed salacca peel to potassium carbonate ratio of 1:4 and fixed potassium carbonate concentration of 20 %-w. The impregnated salacca peels were then carbonized at temperature of 800 °C. Activated carbons with a high surface area of 1939 m2/g were obtained. The activated carbon was tested in the adsorption of methylene blue (MB) from aqueous phase. The adsorption study was realized using batch experiments with synthetic MB solution with various initial concentrations of 20, 30, 40, 50 and 55 ppm. The Langmuir, Freundlich, Temkin and Dubinin Radushkevich adsorption models were used for mathematical description of the adsorption equilibrium, and it was found that the experimental data fitted well to the Langmuir isotherm. Batch adsorption studies, based on the assumption of a pseudo-first-order, pseudo-second-order or intraparticle diffusion mechanism, showed that the kinetic data followed closely a pseudo-second-order rather than a pseudo-first-order mechanism. The adsorption capacity of salacca peel based activated carbons for the removal of MB was found to be 674 mg· g-1. These results indicated the salacca peels derived activated carbons as a potential adsorbent for removal of MB from aqueous solutions.